The Effect of Problem-Based Learning Model with Sasak Local Wisdom on Students' Cognitive Abilities - Suharti, Ati; Mashami, Ratna Azizah (LITPAM, 2024)
This study investigates the effect of Problem-Based Learning (PBL) integrated with Sasak local wisdom on high school students' cognitive abilities, particularly in understanding electrolytes and non-electrolytes. PBL, an active learning approach, encourages students to solve real-world problems, fostering critical thinking and problem-solving skills. When combined with local cultural knowledge, such as the Sasak people's practices, PBL enhances academic learning and strengthens students' cultural identity. The research involved two groups of Grade X students from SMA Islam Al-Azhar NW Kayangan, North Lombok. The experimental group (n = 30) received PBL instruction incorporating Sasak cultural contexts, while the control group (n = 31) followed conventional instruction. Data were collected through pretest-posttest assessments and analyzed using paired and independent sample t-tests. The findings reveal that the experimental group demonstrated significantly higher cognitive gains than the control group. The experimental group had a mean gain score of 28.70 (t = -28.70, p < 0.001), compared to 11.95 (t = -11.95, p < 0.001) for the control group. Students in the experimental group showed improved understanding of scientific concepts, such as conductivity and ionization, through real-life applications related to Sasak culture, like local water sources and traditional purification methods. The results highlight the effectiveness of integrating local wisdom into PBL, improving both students' academic performance and their connection to cultural heritage. The study suggests that PBL with local wisdom is a promising pedagogical approach, enhancing cognitive abilities and providing a more meaningful, culturally relevant learning experience.